The Effect of Using Organik Protein in Feed on Abdominal Fat and Internal Organs of Broiler - Rizki Nur Azizah; Osfar Sjofjan (Faculty of Animal Science, Universitas Gadjah Mada, 2022)
The purpose of this research was to determine the effect of organik protein in feed on the quality of abdominal fat and internal organs in broilers. The material used 500 broilers. Levels of organik protein in feed P0 (0% organik protein); P1 (1.5% organik protein); P2 (3.0% organik protein); P3 (4.5% organik protein) and P4 (6.0% organik protein). The variables measured were abdominal fat and internal organs weight of broiler (heart, liver, gizzard, pancreas and spleen). The data were analyzed by using ANOVA and if it shoes significant different among treatment continued by using Duncan’s Multiple Range Test. The result showed that the treatment gave no significant effect (P>0.05) on abdominal fat and weight of heart, liver and spleen. The use of organik protein in feed can reduce `abdominal fat and improve the performance of internal organs such as the gizzard, liver, spleen, pancreas and heart of broilers